How to eat: 1 vegetarianism, religion and law - Irma Kroeze (The Journal for Transdisciplinary Research in Southern Africa, 2012)
The approach of Critical Legal Studies that law is a cultural artefact that can be criticised is taken as point of departure in this paper. This insight is applied to food as a very important cultural artefact that permeates virtually every aspect of our personal and social lives. The paper then examines three types of restrictive diets, namely Kosher food production, halal food rules and vegetarianism. From this study it concludes that all three perform a vital social function of providing adherents with a unifying and identifying set of rules to foster social coherence. But it also provides adherents with a strong moral foundation that serves to justify a sense of moral superiority. Most importantly, all three these diets rest on a modernist view of morality in which absolute, unquestioning and universal truths are possible. It therefore serves to provide certainty in the postmodern condition of uncertainty and relativism. For that reason this study concludes that vegetarianism is the new religion – it provides people who no longer believe in traditional religions with a new certainty.